Which D’s are the important ones? The effects of regional location and density on driving distance in Oslo and Stavanger - Naess, Petter; Cao, Xinyu (Jason); Strand, Arvid (Journal of Transport and Land Use, 2017)
Based on a study in the Greater Oslo and Greater Stavanger urban areas in Norway, this paper employs quantitative and qualitative research methods to investigate the influences of residential location and neighborhood characteristics on car driving distances. Cross-sectional and quasi-longitudinal analyses show that built environment characteristics — especially the distance from the dwelling to the main city center — influence driving distances in both urban areas. In Stavanger, the impact of inward moving seems to be larger than that of outward moving, possibly reflecting self-selection to the inner city. In the relatively monocentric Greater Oslo, the distance to the city center has a stronger impact on weekday driving than on weekend driving. In the more polycentric Greater Stavanger, where the importance of downtown as a destination for commuting is weaker, the distance to the city center has similar effects on weekday and weekend driving. In Greater Stavanger, distance to the secondary center Sandnes also plays a role although the impact is small. Population density and job density have impacts in Greater Oslo but not in Greater Stavanger, where we instead find a weak effect of local-area job surplus. There is no tendency toward compensatory increased weekend driving among inner-city dwellers in either Greater Oslo or Greater Stavanger.